Solitary facial metastasis of an ileal carcinoid - Dalla Valle, R.; Bordi, C.; Milione, et al., M. (Acta Biomedica Atenei Parmensis, 2003)
We report an unusual case of solitary facial metastasis as first clinical manifestation of an ileal carcinoid. Only one similar case has been reported in the literature. The patient, a 79 years old man, was referred for the excision of a right facial subcutaneous nodule. Pathology showed a soft tissue metastasis of mid-gut carcinoid. After a complete radiological investigation, a small carcinoid of the terminal ileum was found and the patient underwent a right emicolectomy. Pathology confirmed a typical EC cells carcinoid identical to that of the facial tumor. At 2 years of follow-up no clinical or radiological signs of others metastases were found.